2023
DOI: 10.7717/peerj.14844
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of the evolution and expression pattern of the HVA22 gene family in three wild species of tomatoes

Abstract: Wild tomato germplasm is a valuable resource for improving biotic and abiotic stresses in tomato breeding. The HVA22 is widely present in eukaryotes and involved in growth and development as well as stress response, such as cold, salt, drought, and biotic stress. In the present study, we identified 45 HVA22 genes in three wild species of tomatoes. The phylogenetic relationships, gene localization to chromosomes, gene structure, gene collinearity, protein interactions, and cis-acting element prediction of all 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The number of PeHVA22 genes was relatively similar to that observed in citrus (six) (Gomes Ferreira et al, 2019), Amborella trichopoda (seven) and Arabidopsis (five) (Chen et al, 2002). However, it was fewer than the number in tomato (ranges from 14 to 16 in four different species) (Wai et al, 2022;Zhao et al, 2023) and cotton (ranges from 16 to 34 in different species) (Zhang et al, 2023). Previous studies have indicated that the expansion of the HVA22 in tomato and cotton resulted mainly from gene duplication events.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The number of PeHVA22 genes was relatively similar to that observed in citrus (six) (Gomes Ferreira et al, 2019), Amborella trichopoda (seven) and Arabidopsis (five) (Chen et al, 2002). However, it was fewer than the number in tomato (ranges from 14 to 16 in four different species) (Wai et al, 2022;Zhao et al, 2023) and cotton (ranges from 16 to 34 in different species) (Zhang et al, 2023). Previous studies have indicated that the expansion of the HVA22 in tomato and cotton resulted mainly from gene duplication events.…”
Section: Discussionmentioning
confidence: 58%
“…The ABA signaling pathway plays a pivotal role in plant responses to abiotic stresses, regulating numerous stress-responsive genes to facilitate plants in coping with challenging environments. HVA22 is a unique group of ABAinduced genes identified and reported to participate in the response to abiotic stresses in various plants, including Arabidopsis, citrus, tomato and cotton (Brands and Ho, 2002;Chen et al, 2002;Guo and Ho, 2008;Courtney et al, 2016;Gomes Ferreira et al, 2019;Wai et al, 2022;Zhang et al, 2023;Zhao et al, 2023). However, limited studies have explored the HVA22 gene family in passion fruit.…”
Section: Discussionmentioning
confidence: 99%